PEMIDANAAN TERHADAP PEMALSUAN SURAT KETERANGAN HASIL RAPID TEST/SWAB ANTIGEN - Winora, Ejia Elang; Soeskandhi, Hary (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The World Health Organization (WHO), the United Nations health organization, has established the COVID-19 pandemic since March 11, 2022. The spread of this virus so quickly swept the world that it caused many victims to die, including Indonesia. The Covid-19 pandemic entered Indonesia on March 2, 2020, with the first case there were 2 (two) Indonesian citizens domiciled in depok officially declared by President Joko Widodo to have been exposed to the covid 19 virus. Furthermore, the Covid-19 pandemic has hit provinces / regencies / cities throughout Indonesia. Various hospitals in the country at that time were overwhelmed to serve patients exposed to covid 19 due to limited health workers, limited rooms and medicines. Really, the Covid-19 pandemic has destroyed various aspects of people's lives, not only health aspects but also economic aspects. Especially with the enactment of PPKM (Enforcement of Restrictions on Community Activities), so that the community is obliged to provide themselves with a certificate of rapid/swab test results. Seeing the high enthusiasm of the public who take care of the rapid / swab test and the high price of the rapid / swab test, this is used by irresponsible individuals by opening illegal services providing a certificate of rapid / swab results at a relatively cheap price compared to the actual (official) test price. One example is in Decision Number 943/Pid.B/2021/PN.Srg where the defendant, SUPRIYADI bin SAMSU with the intention of seeking profit took the act of making or serving the making of a certificate of rapid test results/antigen swabs illegally (fake) in order to be one of the requirements to travel during the Implementation of Emergency Community Activity Restrictions (PPKM) during the Corona Virus Desease Pandemic 2019 (Covid 19). The topic studied in this study is about the punishment of forgery of certificates of rapid test results / antigen swabs in Decision Number 943 / Pid.B / 2021 / PN.Srg. The research method used is a type of normative legal research, and uses a statute approach, a conceptual approach (Conceptual Approach), and a case approach (Case Approach).